2013
DOI: 10.9734/bjesbs/2013/4026
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Achievement and Retention of Nigeria Students Exposed to Concept in Electronic Works Trade through Reflective Inquiry Instructional Technique

Abstract: This work was carried out in collaboration between all authors. Author OAS designed the study, performed the statistical analysis, and wrote the first draft of the manuscript. Author OIP Peter managed the analyses of the study, managed the literature searches and wrote the protocol. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“…The study found a significant difference between the mean retention scores of undergraduate Social Studies students taught using CAI and those taught with conventional methods. This is in line with the findings of Samuel and Peter (2013), Al-Qahtani and Higgins (2013), Giannousiet al (2014), Giovengo (2014), Sisco, Woodcock, and Eady (2015), Banditvilai (2016) and Gambariet al (2017) which revealed a significant difference in the retention score of students taught using CAI and those taught using conventional methods. However, the findings of Mooneyhan (2012) and Elmeret al (2016) reveal no significant difference between retention level of students taught using CAI and those taught using traditional methods.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The study found a significant difference between the mean retention scores of undergraduate Social Studies students taught using CAI and those taught with conventional methods. This is in line with the findings of Samuel and Peter (2013), Al-Qahtani and Higgins (2013), Giannousiet al (2014), Giovengo (2014), Sisco, Woodcock, and Eady (2015), Banditvilai (2016) and Gambariet al (2017) which revealed a significant difference in the retention score of students taught using CAI and those taught using conventional methods. However, the findings of Mooneyhan (2012) and Elmeret al (2016) reveal no significant difference between retention level of students taught using CAI and those taught using traditional methods.…”
Section: Discussionsupporting
confidence: 87%
“…In studies conducted by Samuel and Peter (2013), Al-Qahtani and Higgins (2013), Giannousiet al (2014), Giovengo (2014), Sisco, Woodcock and Eady (2015), Banditvilai (2016) and Gambari, Shittu, Ogunlade and Osunlade (2017), a significant difference in the retention scores of students taught using CAI and those taught using conventional methods is found. Contrarily, the findings of Mooneyhan (2012) and Elmeret al (2016) revealed no significant difference in the retention levels of students taught using CAI and those taught using traditional methods.…”
Section: Introductionmentioning
confidence: 96%
“…Bataineh et al (2018) discovered a significant difference in favor of female when WhatsApp was used to teach English in Iran while Safitri (2021) discovered a significant difference in favor of male students when exposed to WhatsApp. On the other hand, Owodunmi and Ogundola (2013) discovered a significant gender difference in the retention of students in favor of female. Studies by Achor et al (2013) and Gambari et al (2014) revealed no significant difference in the retention of male and female students.…”
Section: Introductionmentioning
confidence: 99%
“…The disparity in gender and achievement has a lot to do with what the students retain in a specified period. Owodunmi and Ogundola (2013) explain that the term gender is a sociocultural structure that results from a person's biological expectations based on their sex. Gender is used to describe particular cultural and behavioural tendencies that are linked to human males and females.…”
Section: Introductionmentioning
confidence: 99%